Pengaruh Model Pembelajaran Index Card Match (ICM) dengan Problem Posing Berbantuan Software MATLAB terhadap Kemampuan Pemecahan Masalah - Nuraeni, Zuli; Rosyid, Abdul (Jurnal Elemen, 2019)
The purpose of this study is to examine the effect of Index Card Match (ICM) learning model with Problem Posing approach and assisted by MATLAB software to improve problem-solving abilities both overall and reviewed from the students' early mathematical abilities. This research is quasi-experiment research with non-equivalent control group design. The population in this study is all students of class XI SMA N 2 Kuningan, with purposive sampling technique took two classes as a sample. The result of data analysis shows the average of students' initial problem-solving ability in the experimental group is equal to the average of students' initial ability in the control group with a significance value are 0.212. After the treatment, there are differences in problem-solving ability in the experimental class and control class that are 3.38 and p-value of -2.563 with asymp. sig 0.010, the rejection for H0 which means the ability to solve mathematical problems in the experimental class is better than the class control. But there aren’t differences in problem-solving abilities in the experimental class and control class with p-value 0.515 and sig 0.476, the acception for H0 which means there aren’t differences the improvement of mathematical problem-solving ability in the experimental class and the control class.